Relac\~oes do Brasil com a América do Sul após a Guerra Fria: Política externa, integraç\~ao, segurança e energia - Walter Antonio Desiderá Neto; Marcelo Passini Mariano; Raphael Padula; Michelle Carvalho Metanias Hallack; Pedro Silva Barros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Since the end of the Cold War, and especially since the 2000s, due to the increasing significance of regional powers in world politics, in order to understand global transformations, it has become crucial to examine how regional powers have been relating to their neighborhoods, complementing their global behavior analysis. Therefore, this work aims to characterize and analyze Brazilian relations with its neighbors (the other American countries), during 1985-2010, concerning Brazilian foreign policy towards the region, the architecture of regional institutions and the management of regional security and energy integration issues. The text is organized in four sections. After a brief introductory part, in the second section is examined how Brazilian foreign policy towards the neighborhood was designed in accordance with administrations and with shifts in the international scene. The third section brings two exams about South American regional integration: security and energy. These two themes were selected since in both cases it becomes clear how Brazilian behavior determines the prosperity (or not) of regional initiatives. In the end, the fourth section aims to synthesize the arguments, concluding the paper.
Keywords: F15; F53; F59; 330; Brazilian foreign policy; South American integration; Mercosur; Unasur